Answer:
x = -2, y = -5, z = 3
Explanation:
You have to substitute the letter with its real value;
3x = -6
Divide both sides by 3;
x = -2
So now we have to replace x with -2;
x + 3y = -7
-2 + 3y = -17
Add 2 to both sides;
3y = -15
Divide both sides by 3;
y = -5
For the last equation you have to replace x and y since we have the values;
4(-2) - 3(-5) + 6z = 25
-8 + 15 + 6z = 25
7 + 6z = 25
Subtract 7 from both sides;
6z = 18
Divide both sides by 6;
z = 3
Check:
4(-2) - 3(-5) + 6(3) = 25
-8 + 15 + 18
7 + 18 = 25
25 = 25
This mean the values are correct.